Establishing Healthy Eating Habits during Child Development to Reduce the Prevalence of Obesity: Establishing Healthy Eating Habits during Child Development to Reduce the Prevalence of Obesity - Nia Reviani; Yulina Eva Riany (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2022)
Obesity is becoming a major public health problem in the general population lately, affecting children and adults. The numbers of obesity could be diminished by performing healthy eating habits and lifestyles at a child's developmental age as they share the same risk factors and are intimately related. This paper is a literature review using various references from relevant journals to examine problems and find answers to existing problems. References were obtained through search engines, then selected based on their closeness to the topic raised in this study. Environments that have low access to healthy foods such as fresh fruit and vegetables are generally found in areas that have socioeconomic problems or in minority groups; on the contrary, areas or groups that have good access to fast food vendors are usually offering foods that contain high sugar and fat. Healthy eating habits can be formed by providing examples of healthy habits in children and increasing parents' attention to their eating patterns.